Filantropi Islam sebagai Strategi Sosial-Keagamaan dalam Deradikalisasi di Indonesia - Brian Fadli Fauzi; Muhammad Ibnu Fajar; Amin Hamdani (Nidhomiya: Research Journal of Islamic Philanthropy and Disaster, 2026)
Introduction: The phenomenon of radicalization in developing countries often occurs and poses a serious challenge to the security and social stability of these developing countries. Deradicalization efforts should not be limited to security measures alone, but can also be addressed through socio-religious approaches, utilizing Islamic philanthropy to counteract deradicalization, particularly in Indonesia. Research Methods: This study employs a literature review method with a qualitative-descriptive approach. Data were obtained from various secondary sources—such as books, journals, institutional reports, regulations, and relevant official publications—and subsequently analyzed using content analysis techniques. Results: Islamic philanthropy, which encompasses zakat, infaq, sedekah, and waqf, plays a crucial role in strengthening welfare and modernization within religion. One of the factors of radicalism is social and economic inequality. The existence of Islamic philanthropic institutions can address this gap and strengthen their thinking, preventing them from being easily tempted by radicalism. Conclusion: Therefore, philanthropic institutions are required to be managed in a structured and professional manner to achieve prosperity for the people.